2012
DOI: 10.1039/c2dt12334g
|View full text |Cite
|
Sign up to set email alerts
|

Study of the coordination and solution structures for the interaction systems between diperoxidovanadate complexes and 4-(pyridin-2-yl)pyrimidine-like ligands

Abstract: To understand the substitution effects of 4-(pyridin-2-yl)pyrimidine (pprd) on the coordination reaction equilibria, the interactions between a series of the pprd-like ligands and [OV(O(2))(2)(H(2)O)](-) or [OV(O(2))(2)(HOD)](-) or [OV(O(2))(2)(D(2)O)](-) (bpV) have been explored by a combination of multinuclear ((1)H, (13)C, and (51)V) magnetic resonance, heteronuclear single quantum coherence (HSQC) and variable temperature NMR in a 0.15 mol L(-1) NaCl D(2)O solution that mimics physiological conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Generally, it is known that 1 H NMR signals of heteroaromatic rings will be shifted to the downfield region by the coordination of a N atom to a transition‐metal ion. Indeed, for the known pprd complexes of Cu I ,59,60 Ag I ,58 and V V ,76 the 1 H NMR signals were observed in the downfield region relative to those of metal‐free pprd, except for the special case of the sandwich‐shaped Ag I –pprd complexes {[Ag 4 (pprd) 4 ] 2 (XF 6 )}(BF 4 ) 6 · 8MeNO 2 (X = Si, Ge, or Sn) 58. As mentioned in the preceding section, our crystallographic study showed that the pprd ligand is close to the phenyl groups of PPh 3 in the [Ir(H) 2 (PPh 3 ) 2 ] fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is known that 1 H NMR signals of heteroaromatic rings will be shifted to the downfield region by the coordination of a N atom to a transition‐metal ion. Indeed, for the known pprd complexes of Cu I ,59,60 Ag I ,58 and V V ,76 the 1 H NMR signals were observed in the downfield region relative to those of metal‐free pprd, except for the special case of the sandwich‐shaped Ag I –pprd complexes {[Ag 4 (pprd) 4 ] 2 (XF 6 )}(BF 4 ) 6 · 8MeNO 2 (X = Si, Ge, or Sn) 58. As mentioned in the preceding section, our crystallographic study showed that the pprd ligand is close to the phenyl groups of PPh 3 in the [Ir(H) 2 (PPh 3 ) 2 ] fragment.…”
Section: Resultsmentioning
confidence: 99%
“…UiO-67-KVO(O 2 ) 2 (4) was synthesized by preparing the partially metalated ligand and then building the MOF structure. Peroxovanadate precursor solution was prepared following the reported procedure with modification [42]. H 2 bpydc (0.2442 g, 1 mmol) was added into ethanol (20 mL) and suspended using ultrasound for 30 min to form a suspension (a).…”
Section: Synthesis Of Uio-67-kvo(o 2 )mentioning
confidence: 99%
“…Alternatively, UiO-67-WO(O 2 ) 2 and UiO-67-KVO(O 2 ) 2 are both prepared by coordinating first with the organic ligand and then by building the MOF structure. The WO(O 2 ) 2 and KVO(O 2 ) 2 anchored organic ligand were prepared by the standard synthetic method for complexes of the type [MO(O 2 ) 2 L] (L = organic ligand), which involves adding the organic ligand (H 2 bpydc in our case) to the aqueous solution containing the [MO(O 2 ) 2 (M = W and V)] complex and a large excess of H 2 O 2 [41,42]. Please note that the anchoring procedure of the organic ligand is incomplete; only part of the ligand was successfully functionalized.…”
Section: Synthesismentioning
confidence: 99%
“…A series of 1-alkyl-3-methylimidazolium This journal is © The Royal Society of Chemistry 2013 hexafluorocomplex salts [C x MImAF 6 ] (x = 14, 16 and 18; A = P, As, Sb, Nb and Ta) were synthesized and the affect of alkyl chain length and anion size on their thermal and structural properties was examined. 28 32 [Cp 2 VCl 2 ] was used as a catalytic precursor for benzylic C-H oxidation using tert-butyl hydrogen peroxide (TBHP) as the oxidant. 33 The mechanism involves formation of a vanadium(V) oxo radical, which abstracts a hydrogen atom from the weak benzylic C-H bond, forming a vanadium(V) hydroxide and benzylic radical, the latter of which abstracts the hydroxide ligand to form benzylalcohol and a V(IV) intermediate.…”
Section: Niobium and Tantalummentioning
confidence: 99%